War as a factor of stress in higher education students in Ukraine - Kryvoshei, K. Yu.; Кривошей, Кирило Юрійович (Riga : Baltija publishing, 2024)
The outbreak of large-scale military aggression by the Russian Federation against Ukraine has deprived Ukrainian students of their usual and safe way of life. The loss of comfortable study conditions occurred regardless of personal characteristics, social status, academic achievements, political views, and economic conditions of higher education students. War always creates factors that suggest danger to one's own life. Because of this, war is a supernormal extreme situation. Extreme factors require the mobilization of the students’ additional mental and physical resources. These additional resources are needed to overcome an external threat that leads to the development of stress. This makes the military actions in Ukraine an intense and long-term objective cause of stress. The existence of long-term stress among higher education students due to the military conflict is a huge challenge for the modern Ukrainian education system. Stress is associated with the emergence of negative feelings such as fear, despair, sadness, anxiety, helplessness, depression, apathy, etc. In a state of stress, students memorize and reproduce information worse; it is more difficult for them to make decisions; their concentration, attention span and volume deteriorate; their ability to perceive and think decreases, etc. Current research on the level of stress among the population of Ukraine shows us disappointing data. The impact of at least one war-related stressor is experienced by all respondents; a large number of respondents have symptoms that meet the diagnostic criteria for post-traumatic stress disorder or complex post-traumatic stress disorder [3, p. 281]. Common stressors are factors such as hearing an air raid siren, financial difficulties, the need to stay in a shelter, hearing and seeing shellings. In addition to the usual symptoms of stress, a significant part of the Ukrainian population has certain manifestations of anxiety, depression, and insomnia. Due to the state of stress, Ukrainians suffer from memory impairment, appetite problems, fatigue, increased irritability, insomnia, and nightmares. In wartime conditions, the number of stressors affecting students and not related to the learning process has increased significantly. The war has had a significant impact on the psychological state of students, reducing their ability to withstand stress and increasing the intensity and frequency of stress. According to the researches, more than half of the students affected by the war experience stress, and almost two-thirds say that it is difficult for them to overcome this stressful state.
Війна як чинник виникнення стресу здобувачів вищої освіти в Україні
Науковий керівник: Сергій Борисович Бєляєв, доктор педагогічних наук, професор кафедри профільної підготови, Харківський національний університет імені В. Н. Каразіна
Keywords: SOCIAL SCIENCES; war; stress; Ukraine; negative feelings; students; wartime; post-traumatic stress disorder; post-traumatic stress disorder; financial difficulties; the need to stay in a shelter; hearing and seeing shellings